A comparative study of Therapeutic oral hygiene versus conventional oral hygiene among patients having Ryle’s Tube - C. Gholap, Manisha; Shinde, Mahadeo; K. Choudhari, Samir; M.Thomas, Sanila; K. Koshy, Asha; Mathew, Silpa; Pawar, Shubham; Patil, Sneha (International Journal of Psychosocial Rehabilitation, 2020)
Background: Patients with Ryle’s Tube may be more vulnerable to oral disease and discomfort than the general population and may be unable to care for themselves. Oral health is a functional, structural, physiologic, and psychosocial statee of well-being and essential to an individual’s general health and quality of life. Objective: To compare the effect of therapeutic oral hygiene and conventional oral hygiene among patients having Ryle’s tube. Methods: An experimental research design was used to conduct the study among patients admitted to the general wards, and a total of 64 patients were selected by purposive sampling technique and further divided into 32 in the experimental group and 32 in the control group. Data was collected by using a structured questionnaire. Informed written consent was obtained from all the participants. An oral hygiene assessment tool was used to assess the oral condition. To the experimental group, 4-hourly mouthwash is given with sodium chloride and sodium bicarbonate, and to the conventional group, regular hospital routine management is followed. After 5 days, oral condition was assessed to compare the effect of the methods. Results: The mean of the experimental group was 10.406 with an SD of 1.103, and the mean of the control group was 2.468 with an SD of 1.244. The calculated t-value was7, which was found to be statistically significant at the level of 0.0001. Conclusion: Study results conclude that the therapeutic method was found effective to improve the oral hygiene of patients with Ryles tubes.